Mesiodistal and buccolingual crown size and height of deciduous teeth from a tooth bank in Brazil - Taciana Emília de Almeida Anfe; Yuri Arakaki; Denise Moral Nakamura; Glauco Fioranelli Vieira (Brazilian Dental Science)
Objective: The size of primary teeth in the current Brazilian population has not been studied; the aim of this in vitro study was to measure anterior and posterior deciduous teeth in respect to mesiodistal, buccolingual and crown height sizes. Methods: A sample of 1095 deciduous teeth was obtained from a tooth bank at Dental School from São Paulo University. The measurements were made with a digital caliper. Only unworn, undamaged teeth were measured. Results: In mesiodistal diameter, maxillary central incisor showed the highest variation and first mandibular molar showing the least. In buccolingual sizes, mandibular second molar was the tooth with higher variability. Conclusion: This study provides a complete record of deciduous teeth size in Brazilian children. There was an evident variation of size of the primary teeth.